Overexpression of squalene synthase in withania somnifera leads to enhanced withanolide biosynthesis - Patel, Neha; Patel, Parth; Kendurkar, Shuchishweta V.; Thulasiram, Hirekodathakallu V.; Khan, Bashir Mohammad (Plant Cell Tissue and Organ Culture, 2015)
Genetic engineering of secondary metabolic pathways is an emerging area of research for production and improvement of natural products in plant biotechnology. Here, we describe a systematic approach to manipulate a key regulatory step of isoprenoid biosynthetic pathway in Withania somnifera to study its effect on withanolide production. We generated T-0 W. somnifera plants overexpressing squalene synthase (WsSQS) by Agrobacterium tumefaciens mediated transformation, which were analyzed by Gus biochemical assay and PCR of hygromycin phosphotransferase (hptII) and WsSQS. qRT-PCR analyses of various transformed tissues indicated 2-5 fold increase in WsSQS transcripts in both T-0 and T-1 generations. The tissue specific protein expression studies revealed 2-3 fold increase in WsSQS, which was further confirmed by enzyme activity. These observations were corroborated with the 1.5-2 fold increase in total withanolide content of the transformed tissues. However, in leaf tissue, the levels of Withaferin A and Withanolide A increased significantly up to 4-4.5 fold. These findings demonstrate genetic engineering of isoprenoid pathway in W. somnifera resulting in enhanced production of withanolides, and also provide insights into such metabolic pathways for their manipulation to improve the pharmacological content of different medicinally important plants.
Keywords: Agrobacterium tumefaciens; Solanaceae; Squalene synthase; Withania somnifera; Withanolides